The Faulty Perinatal Hormonal Imprinting as Functional Teratogen - Csaba, G. (Current Pediatric Reviews, 2016)
Perinatally, the developmental window for the adjustment of hormone receptors to their target hormones is open. The hormonal imprinting which determines the relationship of hormones and receptors for life takes place in this period. The recognition ability of developing receptors is not yet entirely specific, so they could be ‘cheated’ by false imprinters such as related hormones, drugs, environmental pollutants or certain food components and faulty imprinting may result. This causes a functional developmental abnormality, which is then manifested, at any later time in life, as the alteration of the binding capacity of hormone receptors. With or without the presence of other factors this could cause problems in hormone regulated functions or may result in diseases. So it may be stated that faulty hormonal imprinting, caused by a broad spectrum of receptor level molecules, is acting as a functional teratogen. This means that functional maldevelopment is not restricted to intrauterine life, but can also occur after birth, in the perinatal period. The inclusion of faulty imprinting as maldevelopment widens both the list of functional teratogens and the period of teratogenicity. The importance and danger of faulty imprinting is high, especially considering its heritable (transgenerational) character. Considering the facts, the attitudes in the present-day perinatal treatments and medical training must be changed.
Keywords: epigenetics